Development of the tool steel heating technology - V. I. Timoshpolsky; A. B Steblov; V. V. Filippov; V. S. Timofeev; V. A. Tischenko; D. V. Lenartovic (Литьë и металлургия, 2001)
The data on the technology of heating and thermal treatment of a new branch of steel for the hot deformation dies are set forth in the article.